2020
DOI: 10.1212/nxi.0000000000000815
|View full text |Cite
|
Sign up to set email alerts
|

CSF chitinase 3-like-1 association with disability of primary progressive MS

Abstract: ObjectiveTo assess the role of CSF chitinase 3-like-1 (CHI3L1), chitinase 3-like-2 (CHI3L2), and neurofilament light chain (NfL) in predicting the course of primary progressive MS (PPMS).MethodsWe analyzed CSF CHI3L1, CHI3L2, and NfL levels in 25 patients with PPMS with disease duration ≤10 years and no disease-modifying therapy for ≥6 months from the prospective Understanding Primary Progressive Multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 11 publications
2
22
0
1
Order By: Relevance
“…Interestingly, we observed that the presence of monocytes/macrophages was associated with conversion to CDMS. This underlines findings on Chitinase 3like 1 (CHI3L1), a glycoprotein secreted by macrophages (41), which was determined as a biomarker in MS (42)(43)(44) and which was also associated with the conversion from CIS to CDMS (45).…”
Section: Discussionsupporting
confidence: 76%
“…Interestingly, we observed that the presence of monocytes/macrophages was associated with conversion to CDMS. This underlines findings on Chitinase 3like 1 (CHI3L1), a glycoprotein secreted by macrophages (41), which was determined as a biomarker in MS (42)(43)(44) and which was also associated with the conversion from CIS to CDMS (45).…”
Section: Discussionsupporting
confidence: 76%
“…The relevance of CSF CHI3L1 to neurologic disability in PMS was recently reported. 30 In PMS compared with RMS, higher levels of spinal cord atrophy are common findings. 31 …”
Section: Discussionmentioning
confidence: 99%
“…In a recent prospective study of 607 patients over 12 years in which serum NfL was measured using Simoa assay, a significant relationship was found between EDSS deterioration and NfL serum levels. However, no association was found between serum NFL levels and long-term disease progression in relapsing and between CSF NFL levels and EDSS scores in primary progressive forms ( 110 , 111 ). These results are contradictory to those found by Barro and Disanto in two different studies, where a correlation was found between high serum NfL levels and long term disability progression in MS ( 112 , 113 ).…”
Section: Biomarkers Associated With Disability Progressionmentioning
confidence: 83%